Sterilization Policy with Incomplete Information: Peru 1995-2000 - Silvio Rendon (Institute of Labor Economics (IZA), 2020)
In this research I investigate what percentage of female sterilizations performed in Peru from 1993 to 2000 were done providing adequate information to their users for a free decision about their adoption. I use data from ENDES/DHS 2000, which contains detailed information about contraceptive methods adopted in those years, with especial emphasis on sterilizations. I make a descriptive analysis, a projection of total sterilizations, and an estimation of the probability that a woman be sterilized. I find a large use of sterilizations as a contraceptive method between 1995 and 1997: more than 36% of women that used a contraceptive method were sterilized. I also find that a large percentage of women were not adequately informed about sterilizations: only 35% of sterilized women was given complete information, that is, that they will have no more children, about side effects, what to do about them, and that there were alternative contraceptive methods. With additional data from MINSA I calculate that 211,000 sterilized women did not receive complete information from 1993 to 2000, of which 25,000 sterilized women did not receive information that the sterilization implied not being able to have more children. I also estimated that not receiving complete information increased the probability that a women is sterilized in 10 percentage points.
Keywords: J13; I15; J16; 330; health policy; fertility; sterilization; family planning; development